Risk Control of Work Accidents in the Overpass Steel Box Girder Erection Work Process with JSA and HIRADC Methods - Muhammad Yoris Saeful Siesmax; Muhamad Oka Mahendra (CIVED, 2025)
The construction of bridges, flyovers, overpasses, and other types of crossing structures is increasing along with the increasing volume of traffic. One important aspect of this development is the Girder Erection process, which is highly risky because heavy equipment and materials are in direct contact with workers. This study aims to analyze the risk of work at each stage of the construction of the Steel Box Girder Overpass Balaraja Barat B Tangerang City using the Job Safety Analysis (JSA) and Hazard Identification Risk Assessment and Determining Control (HIRADC) methods. This analysis covers each stage of work, starting from preparation, crawler crane setup, Steel Box Girder assembly, and Erection. The results showed 5 jobs with low-risk levels, 6 jobs with high-risk levels, and 7 jobs with very high-risk levels. In the research findings, the factor that causes the dominance of high and very high-risk levels is due to the impact of the risks that arise many of which have a very fatal impact so that they can cause large material losses and can cause casualties. Therefore, the determination of risk control is carried out to reduce the risk level to a lower level. After controlling, the risk level results are 11 jobs with low-risk levels, 6 jobs with moderate risk levels, and 1 job with high risk.